Poor Student Grades: Identifying the Underlying Reason - Wall, Andrew (ADA University, 2023)
This study aimed to determine if relationships between general emotional intelligence, dimensions of attribution styles (locus of control and stability of attributions), and English language scores could be found in the Azerbaijani context. Cronbach's alpha, a measure of internal consistency, was calculated for both the general emotional intelligence survey (SSEIT) and the dimensions of attribution survey, generating acceptable reliability scores. 120 students, who were at least 18 years of age, within our English for Academic and Professional Purposes program (EAPP) were asked to respond to the surveys of which 52 completed them (18 males and 34 females). Female students scored 7.76 points higher on the emotional intelligence test than their male counterparts. Interestingly, a significant relationship was detected for the 18 male students when performing multiple linear regression using the independent variables, emotional intelligence and dimensions of attribution style, against the dependent variable English language use (grammar) score. The multiple regression model explained 32% (Adjusted R2 = .32, F (481.93,52.79) =9.13, p = .008) of variance in the dependent variable, student language use score, which may be attributed to the independent variable, emotional intelligence (SSEIT) score.
Keywords: Academic achievement -- Azerbaijan; Gender differences -- Academic performance; English language -- Study and teaching -- Azerbaijan; Azerbaijan -- Education system; Education